A new set of highly efficient primers for COI amplification in rotifers - Zhang, Yanan (Mitochondrial DNA B Resour, 2021)
Rotifers are a small-sized but key group of freshwater zooplankters with high species richness, linking primary producers to higher consumers in aquatic food webs. DNA barcoding has been widely used in exploring its biodiversity, cryptic speciation and phylogeny. However, the inefficiency of universal primers to amplify COI of rotifers hinders our understanding of their species richness and genetic diversity. Here, we develop a new pair of primers, 30 F and 885 R, to amplify the COI gene of rotifers. We used 22 species to test their PCR success rate and found that the new pair of primers was more efficient (86%) than two pairs of universal primers, namely, dgLCO and dgHCO (32%), and Folmer primers (59%). The new primers will allow the barcoding of groups that were so far difficult to sequence and will contribute to clarify species diversity and phylogeny of rotifers.